a) $\sum_{i=1}^{p-1}\left [ \frac{i^2}{p} \right ]=\sum_{i=1}^{p-1}\frac{i^2}{p}-\sum_{i=1}^{p-1}\left \{ \frac{i^2}{p} \right \}=\frac{\left ( p-1 \right )p\left ( 2p-1 \right )}{6p}-\sum_{i=1}^{p-1}\left \{ \frac{i^2}{p} \right \}$
Với mỗi số $a \in\left \{ 1;2;...;p-1 \right \}$ bất kì, tồn tại duy nhất số $b\in\left \{ 1;2;...;p-1 \right \}$ để $a^2+b^2 \vdots p$.
Do đó ta có thể chia $\left \{ 1;2;...;p-1 \right \}$ thành $\frac{p-1}{2}$ cặp $\left(a;b\right)$ để $a^2+b^2 \vdots p$.
Khi đó: $\sum_{i=1}^{p-1}\left \{ \frac{i^2}{p} \right \}=\sum_{a,b}^{}\left(\left \{ \frac{a^2}{p} \right \} +\left \{ \frac{b^2}{p} \right \} \right)=\frac{p-1}{2}$, do đó$\sum_{i=1}^{p-1}\left [ \frac{i^2}{p} \right ]=\frac{\left ( p-1 \right )p\left ( 2p-1 \right )}{6p}-\frac{p-1}{2}$.